Differences in Nonspecific Low Back Pain between Young Adult Females with and without Lumbar Scoliosis - Wangshu Yuan; Jianxiong Shen; Lixia Chen; Hai Wang; Keyi Yu; Hui Cong; Jingya Zhou; Youxi Lin (Pain Research and Management)
Study design. Retrospective characterization of nonspecific low back pain (NSLBP) in young adult female patients with and without lumbar scoliosis. Background. There is no consensus as to whether NSLBP in scoliosis patients is related to scoliosis per se or is just a normal symptom that could happen in anyone. Objectives. The aim of this study was to compare the differences in NSLBP between young adult female patients with and without lumbar scoliosis and to provide a theoretical basis for differential treatment of NSLBP in patients with and without lumbar scoliosis. Methods. Ninety female young adults with NSLBP were divided into scoliosis and nonscoliosis groups. Characteristics of pain, lumbar mobility, muscle strength, Cobb angle, axial trunk rotation (ATR) angle, and surface electromyography (SEMG) signal were compared between the two groups. Results. The pain location in scoliotic patients was more concentrated on the left side of the lumbar spine (P≤0.001). The area affected by pain (P=0.028) and the numerical pain rating scale (NPRS) scores (P=0.014) of scoliotic patients were less than those of nonscoliotic patients. The difference between side-bending in scoliotic patients was greater than that in nonscoliotic patients (P=0.001). Scoliotic patients exhibited a significantly better ability for flexion (P=0.001) and extension (P=0.017) than nonscoliotic patients. The posterior muscles in scoliotic patients were stronger than those in nonscoliotic patients (P=0.014). The ratio of root-mean-square (RMS) on paraspinal muscles in scoliotic patients was greater than that in nonscoliotic patients (P≤0.001). Scoliotic patients exhibited greater relaxation time during the flexion-relaxation phenomenon (FRP) than nonscoliotic patients (P=0.024). Conclusions. The characteristics of NSLBP experienced by patients with lumbar scoliosis were distinct from those of NSLBP experienced by nonscoliotic patients. The treatment of NSLBP in scoliotic patients should be different from that in nonscoliotic patients.